A cellulose acetate-based interfacial polymerization flat nanofiltration membrane and preparation method thereof
By using methyl acetate as a cosolvent in cellulose acetate ultrafiltration membrane and performing interfacial polymerization, a cellulose acetate-based nanofiltration membrane with high retention and large water flux was prepared, which solved the problems of poor performance, harmful cosolvents and inconsistent with sustainable development in the prior art.
Patent Information
- Application Number
- CN202310140512.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The existing preparation methods of cellulose acetate nanofiltration membranes have problems such as poor performance, harmful to human health and the environment, and interfacial polymerization is mainly carried out on petroleum-based polymer membranes, which is difficult to meet the requirements of sustainable development.
Ultrafiltration membranes were prepared by non-solvent induced phase separation using cellulose acetate as raw material, and economical and environmentally friendly cosolvent methyl acetate was used to regulate the membrane structure. By selecting suitable aqueous and oily monomers for interfacial polymerization, a cellulose acetate-based nanofiltration membrane with salt cutoff properties was prepared.
It achieves higher interception effect and greater water flux of cellulose acetate ultrafiltration membrane, reduces the harm of the aid solvent to human health and the environment, and meets the requirements of sustainable development.
Smart Images

Figure CN116422164B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of natural polymer materials, and in particular relates to a cellulose acetate-based interfacial polymerization flat nanofiltration membrane and a preparation method thereof. Background Art
[0002] Clean and safe water is one of the most indispensable resources for humans and ecosystems. However, due to population growth, droughts caused by climate change and toxic industrial waste, water sources are constantly drying up. In order to meet the world's growing demand for clean water, more advanced water treatment technologies must be developed. At present, water purification technologies include chemical precipitation, ion exchange, evaporation, reverse osmosis and membrane filtration. As an environmentally friendly and energy-saving technology, membrane separation plays an increasingly important role in water treatment. Among them, separation membranes can be divided into microfiltration, ultrafiltration and nanofiltration due to their membrane pore size. The substances filtered by different pore sizes are also different, and their application fields will also be different. Ultrafiltration uses pressure as a driving force to intercept colloids and protein molecules with a particle size of 10-100 nm, while passing smaller inorganic salts, dyes and solvents. Its interception relative molecular mass is generally controlled between 103-106Da, and it is usually set before the nanofiltration process to achieve the effect of pre-separation. The pore size range of nanofiltration membranes is 1~10 nm, and the molecular weight cutoff is between 200~1000 Da. It has significant advantages in drinking water purification, seawater desalination, and wastewater treatment. Organic membrane materials are widely used in the market, which are mainly divided into two categories: organic synthetic polymer membranes and natural polymer membranes. In the membrane separation process, organic synthetic polymer membrane materials such as polysulfone, polyurethane, polyolefin, and fluorine-containing are widely used. However, although the separation effect of organic synthetic polymer membranes is good, their raw materials are non-renewable resources and do not meet the requirements of human sustainable development. Cellulose acetate, as one of the cellulose derivatives, has the advantages of good hydrophilicity, large water permeability, high chlorine resistance, and good film-forming properties. It has irreplaceable advantages over organic synthetic polymer membranes. The preparation of cellulose acetate ultrafiltration membranes using cellulose acetate as a raw material has gradually developed. Non-solvent induced phase separation is an important method for preparing cellulose acetate ultrafiltration membranes. It is a process of obtaining ultrafiltration membranes by causing phase separation caused by diffusion and penetration of non-solvents into polymer solutions. The performance of ultrafiltration membranes is related to various indicators of the ultrafiltration process. The preparation of ideal ultrafiltration membranes requires the selection of appropriate solvents. In recent years, co-solvents have been widely used in the manufacture of ultrafiltration membranes by phase separation, which provides more freedom for adjusting the structure and performance of the membranes. A high-density ultrafiltration membrane with higher solute rejection can be manufactured by using co-solvents. Existing co-solvents used to regulate the structure of cellulose acetate ultrafiltration membranes include acetone, tetrahydrofuran, etc. They have excellent film-forming properties and strong solubility for cellulose acetate.
[0003] At present, most of the preparation of cellulose acetate nanofiltration membranes is to mix multiple solvents, and then perform solvent exchange treatment or heat treatment on the membrane by phase inversion method. However, compared with interfacial polymerization thin film composite membrane (TFC), its performance is poor. As an important part of the modern nanofiltration membrane production industry, interfacial polymerization mainly selects suitable aqueous phase monomers and oil phase monomers to form an active layer (usually a polyamide layer) on the substrate. The formation of the active layer and the performance of the entire thin film composite (TFC) membrane are well affected by the physicochemical properties of the supporting layer material. In this regard, the performance of the bottom substrate and the top barrier membrane can be optimized separately to achieve the desired permeability and selectivity. However, most of the more mature supporting layer materials on the market are based on petroleum, which has a greater environmental pollution.
[0004] Therefore, the prior art has the following disadvantages: 1) The ultrafiltration membrane materials widely used in the market include polysulfones, polyurethanes, polyolefins, fluorine-containing materials, etc. However, these organic synthetic polymer materials have some disadvantages: they cause great environmental pollution during the synthesis process, have high material costs, and are non-renewable resources. 2) The co-solvents widely used in the market for preparing cellulose acetate ultrafiltration membranes include acetone, tetrahydrofuran, etc. However, these co-solvents have some disadvantages: acetone and tetrahydrofuran are very harmful to human health and the environment. Acetone is prone to cause safety accidents and is subject to national control. Tetrahydrofuran is a Class 2B carcinogen in the list of carcinogens published by the World Health Organization's International Agency for Research on Cancer. Although the use of acetone, tetrahydrofuran, etc. as co-solvents can regulate the structure of cellulose acetate ultrafiltration membranes to a certain extent, it is difficult to solve human health and environmental problems. 3) Interfacial polymerization is widely used in petroleum-based polymer membranes, which does not meet the requirements of sustainable development. Summary of the invention
[0005] In view of the above problems, the present invention uses cellulose acetate as a raw material to prepare an ultrafiltration membrane, and uses economical and environmentally friendly co-solvent methyl acetate to regulate the structure of the cellulose acetate ultrafiltration membrane, thereby reducing the harm to human health and the environment caused by the co-solvent. By selecting appropriate aqueous phase monomers and oil phase monomers, the prepared ultrafiltration membrane is subjected to interfacial polymerization to prepare a cellulose acetate-based nanofiltration membrane with salt interception performance.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a cellulose acetate-based interfacial polymerization flat nanofiltration membrane comprises the following steps:
[0008] (1) Preparation of casting solution
[0009] Before preparing the casting solution, the cellulose acetate powder was placed in a 60°C oven and dried for 24 hours. Subsequently, a certain amount of cellulose acetate powder was weighed and dissolved in a solution containing a certain proportion of N,N-dimethylacetamide and methyl acetate, and stirred at room temperature for 6 hours. Then, the agitator was turned off, vacuumed or allowed to stand for degassing for 4 hours to obtain a uniform and transparent cellulose acetate casting solution. Among them, the mass fraction of cellulose acetate was 16~20 wt%.
[0010] (2) Ultrafiltration membrane production by phase inversion method
[0011] Cellulose acetate ultrafiltration membrane: Use a 200um thick casting knife to evenly coat the degassed cellulose acetate casting solution on the surface of non-woven fabric or glass plate. After 30 seconds of solvent evaporation, immerse the obtained cellulose acetate primary membrane in deionized water at room temperature to solidify into a membrane. Wash the prepared membrane with deionized water 3 times to remove the residual mixed solvent, and then store it in deionized water for testing.
[0012] The specifications of the above-mentioned cellulose acetate raw material are: 39.8 wt% acetyl content and molecular weight of 30,000.
[0013] (3) Preparation of cellulose acetate-based nanofiltration membrane by interfacial polymerization
[0014] Prepare a 2 g / l diethylenetriamine aqueous solution and a 1 g / l 1,3,5-benzenetricarboxylic acid chloride n-hexane organic solution for later use; immerse the cellulose acetate ultrafiltration membrane obtained in step (2) in the prepared aqueous solution for 15-30 min, then take out the cellulose acetate membrane and gently wipe the residual liquid on the membrane surface with filter paper; then immerse the membrane in the prepared oil phase solution for 5 min, then take out and put it in a 60°C oven for 5-10 min, so that the polymerization product of the reaction of ethylenetriamine and 1,3,5-benzenetricarboxylic acid chloride can be evenly and firmly attached to the surface of the cellulose acetate ultrafiltration membrane. Thus, the preparation of the cellulose acetate nanofiltration membrane is completed.
[0015] The aqueous phase monomer in the aqueous phase solution may also be one of polyethyleneimine, piperazine, m-phenylenediamine, 1,3-cyclohexanebis(methylamine), triethylenetetramine, etc., preferably diethylenetriamine, polyethyleneimine or piperazine.
[0016] The present invention regulates the structure of cellulose acetate flat ultrafiltration membrane by a novel co-solvent methyl acetate to achieve a higher retention effect of cellulose acetate ultrafiltration membrane on bovine serum albumin. The preparation method of cellulose acetate ultrafiltration membrane is non-solvent (water) induced phase separation. The specific steps of the process are: first, a homogeneous coating solution composed of a polymer, a solvent or some other non-solvent substances is prepared. Subsequently, the solution is cast into a membrane and then immersed in a coagulation bath (such as water). The principle of the process is to infiltrate the non-solvent into the polymer solution, thereby causing the separation between the polymer-rich phase and the discontinuous polymer-poor phase in the polymer. The dissolution of cellulose acetate is a physical and chemical process through the gradual solvation of the -OH group and the -OCOCH3 group on its molecule, and the weakening of the attraction between cellulose acetate molecules. Methyl acetate has two forces with cellulose acetate, one is hydrogen bonding and the other is dipole-dipole interaction, in which hydrogen bonding is dominant. The structure of cellulose acetate ultrafiltration membrane is precisely regulated by the volatility and plasticization of methyl acetate. The prepared cellulose acetate ultrafiltration membrane has good water flux and high retention rate.
[0017] The nanofiltration membrane is prepared by selecting triethylenediamine as the aqueous phase monomer and 1,3,5-benzenetricarboxylic acid chloride as the oil phase monomer to carry out interfacial polymerization on a cellulose acetate ultrafiltration membrane substrate. The prepared nanofiltration membrane has good retention performance.
[0018] The beneficial effects of the present invention are:
[0019] (1) In the non-solvent induced phase separation membrane process, there are multiple interactions of non-equilibrium processes. Among them, the choice of solvent-cosolvent system is a key factor affecting the structure and performance of ultrafiltration membranes. First, cellulose acetate with a content of 20 wt% was selected as the raw material, and the structure of cellulose acetate ultrafiltration membrane was precisely controlled by adjusting the ratio of N,N-dimethylacetamide and methyl acetate, so as to achieve better ultrafiltration performance of cellulose acetate membrane.
[0020] (2) Interfacial polymerization is usually carried out on a petroleum-based polymer support membrane, and rarely on a cellulose acetate base membrane. The present invention selects a suitable cellulose acetate ultrafiltration membrane as a support material, and performs interfacial polymerization on the base membrane by configuring a 2 g / l diethylenetriamine aqueous phase solution and a 1 g / l 1,3,5-benzenetricarboxylic acid chloride n-hexane organic phase solution to make the polyamide active layer evenly attached to the cellulose acetate base membrane, thereby achieving efficient salt interception.
[0021] (3) Methyl acetate is mainly used in the production of resins, coatings, adhesives, and leather in industry, but has not yet been used in the preparation of cellulose acetate flat membranes. Methyl acetate is cheap and readily available, and has a strong solubility for cellulose acetate. Compared with other traditional co-solvents (such as acetone, tetrahydrofuran, etc.), it is less harmful to human health and the environment. In addition, the cellulose acetate ultrafiltration membrane prepared by it has the characteristics of high retention, large water flux, high strength, and anti-pollution, and can be used on a large scale for commercial purposes. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The performance test diagram of the blank ultrafiltration membrane (M0, the solvent is N, N-dimethylacetamide) and the optimized ultrafiltration membrane (M2, the solvent is N, N-dimethylacetamide and methyl acetate (mass ratio is 3:1));
[0023] Figure 2 This is the morphology of cellulose acetate ultrafiltration membrane;
[0024] Figure 3 To test the separation performance of cellulose acetate nanofiltration membrane;
[0025] Figure 4 This is a comparison of the morphologies of cellulose acetate ultrafiltration membrane (M2) and cellulose acetate nanofiltration membrane (NF). DETAILED DESCRIPTION
[0026] In order to further disclose but not limit the present invention, the present invention is further described in detail below with reference to examples.
[0027] Example 1
[0028] At room temperature, with N,N-dimethylacetamide as solvent and methyl acetate as co-solvent (the mass ratio of solvent to co-solvent is 3:1), pour 20 wt% of cellulose acetate into the above mixed solvent, stir at 400 r / min for 6 hours, then turn off the stirrer, evacuate or let stand for degassing for 4 hours to obtain a uniform and transparent cellulose acetate casting solution.
[0029] Use a 200 um thick film casting knife to evenly coat the degassed cellulose acetate casting liquid on the surface of non-woven fabric or glass plate. After 30 seconds of solvent evaporation, the obtained cellulose acetate primary membrane is immersed in deionized water at room temperature to solidify into a membrane to obtain a cellulose acetate ultrafiltration membrane.
[0030] A 2 g / l diethylenetriamine aqueous solution and a 1 g / l 1,3,5-benzenetricarboxylic acid chloride n-hexane organic solution were prepared for use; the obtained cellulose acetate ultrafiltration membrane was immersed in the prepared aqueous solution for 15 minutes, and then the cellulose acetate membrane was taken out, and the residual liquid on the surface of the membrane was gently wiped with filter paper; then the membrane was immersed in the prepared oil phase solution for 5 minutes, and then taken out and placed in a 60°C oven for 5 minutes to obtain the cellulose acetate flat nanofiltration membrane.
[0031] Cellulose acetate ultrafiltration membrane performance test: pure water flux is 188.0 L / m 2 h, the retention rate of bovine serum albumin was 95.2%.
[0032] Cellulose acetate flat nanofiltration membrane performance test: pure water flux is 14.9 L / m 2 h, the retention rate for Na2SO4 solution is 92.7%, the retention rate for MgSO4 solution is 91.8%, the retention rate for MgCl2 solution is 84.2%, and the retention rate for NaCl solution is 54.1%; the retention rate for Bengal rose red and Congo red solutions is >99%, the retention rate for methyl orange solution is 95.5%, and the retention rate for methylene blue solution is 96.1%.
[0033] Example 2
[0034] The preparation process of cellulose acetate ultrafiltration membrane is the same as that in Example 1.
[0035] A 2 g / l polyethyleneimine aqueous solution and a 1 g / l 1,3,5-benzenetricarboxylic acid chloride n-hexane organic solution were prepared for use; the obtained cellulose acetate ultrafiltration membrane was immersed in the prepared aqueous solution for 15 minutes, and then the cellulose acetate membrane was taken out, and the residual liquid on the surface of the membrane was gently wiped with filter paper; then the membrane was immersed in the prepared oil phase solution for 5 minutes, and then taken out and placed in a 60°C oven for 5 minutes to obtain the cellulose acetate flat nanofiltration membrane.
[0036] Cellulose acetate flat nanofiltration membrane performance test: pure water flux is 31.0 L / m 2 h, the retention rates for Na2SO4 solution are 61.6%, for MgSO4 solution are 88.0%, and for NaCl solution are 69.2%.
[0037] Example 3
[0038] The preparation process of cellulose acetate ultrafiltration membrane is the same as that in Example 1.
[0039] A piperazine aqueous solution with a concentration of 2 g / l and an organic phase solution of n-hexane containing 1 g / l 1,3,5-benzenetricarboxylic acid chloride were prepared and set aside; the obtained cellulose acetate ultrafiltration membrane was immersed in the prepared aqueous solution for 15 minutes, and then the cellulose acetate membrane was taken out, and the residual liquid on the surface of the membrane was gently wiped with filter paper; then the membrane was immersed in the prepared oil phase solution for 5 minutes, and then taken out and placed in a 60°C oven for 5 minutes to obtain the cellulose acetate flat nanofiltration membrane.
[0040] Cellulose acetate flat nanofiltration membrane performance test: pure water flux is 32.2 L / m 2 h, the retention rate of Na2SO4 solution is 86.5%, the retention rate of MgSO4 solution is 75.7%, and the retention rate of NaCl solution is 29.6%.
[0041] Figure 1 The pure water flux and retention rate of bovine serum albumin of the blank ultrafiltration membrane (M0, solvent is N,N-dimethylacetamide) and the optimized ultrafiltration membrane (M2, solvent is N,N-dimethylacetamide and methyl acetate (mass ratio is 3:1)). Among them, the pure water flux of M0 is 405.9 L / m 2 h, and the retention rate of bovine serum albumin was 74.8%. The pure water flux of M2 was 188.0 L / m 2 The retention rate of h for bovine serum albumin was 95.2%.
[0042] Figure 2 The morphological test images (SEM, AFM) of M0 and M2 show that the Ra value of M2 (average roughness (Ra) = 1.55 nm) is reduced compared with M0 (average roughness (Ra) = 2.59 nm), indicating that the addition of methyl acetate leads to a smooth membrane surface, which is confirmed by the SEM surface morphology. The reduction in roughness is due to the faster volatilization effect of MAC on the membrane surface. The SEM cross-sectional images of M0 and M2 were studied, showing an asymmetric microstructure, including a dense surface layer and a porous sublayer composed of large finger-like pores. Compared with M0, M2 has a thicker cortex accompanied by a large number of sponge-like pores, which may indicate that M2 has a better repellency against BSA.
[0043] Figure 3 In order to use M2 as an ultrafiltration substrate, the surface of the membrane was subjected to interfacial polymerization (Example 1) to prepare a cellulose acetate nanofiltration membrane. The pure water flux was 14.9 L / m 2h, the retention rate of Na2SO4 solution is 92.7%, the retention rate of MgSO4 solution is 91.8%, the retention rate of MgCl2 solution is 84.2%, and the retention rate of NaCl solution is 54.1%; the retention rate of Bengal rose red and Congo red solution is more than 99%, the retention rate of methyl orange solution is 95.5%, and the retention rate of methylene blue solution is 96.1%. The performance test of the prepared nanofiltration membrane shows that the polyamide active layer is successfully loaded on the cellulose acetate ultrafiltration membrane, which achieves efficient salt interception of the cellulose acetate nanofiltration membrane.
[0044] Figure 4 The morphology comparison of cellulose acetate ultrafiltration membrane (M2) and cellulose acetate nanofiltration membrane (NF) shows that the average roughness of cellulose acetate nanofiltration membrane is 8.43nm, indicating that its surface is rougher than that of ultrafiltration membrane. The SEM cross-sectional image shows that the polyamide layer formed by interfacial polymerization is successfully loaded on the cellulose acetate ultrafiltration membrane.
[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a cellulose acetate-based interfacial polymerization flat nanofiltration membrane, characterized in that: The following steps are involved: (1) Preparation of casting solution: Dry cellulose acetate powder, then dissolve it in N,N-dimethylacetamide and methyl acetate solution, stir and stand for degassing to obtain a uniform and transparent cellulose acetate casting solution; (2) Preparation of ultrafiltration membrane by phase inversion method: The cellulose acetate casting solution of step (1) is uniformly coated on the surface of non-woven fabric or glass plate. After 30 seconds of solvent evaporation, the obtained cellulose acetate primary membrane is immersed in deionized water at room temperature to solidify into a membrane, thereby obtaining a cellulose acetate ultrafiltration membrane; (3) Preparation of cellulose acetate-based nanofiltration membrane by interfacial polymerization method: first prepare an aqueous phase solution and an organic phase solution of 1,3,5-benzenetricarboxylic acid chloride in n-hexane and set them aside; then immerse the cellulose acetate ultrafiltration membrane obtained in step (2) in the prepared aqueous phase solution for 15-30 min and then take it out; then immerse it in the prepared organic phase solution for 5 min, then take it out and dry it to obtain a cellulose acetate-based interfacial polymerization flat nanofiltration membrane; The mass ratio of N,N-dimethylacetamide and methyl acetate is 3:1; The concentration of the aqueous phase solution is 2 g / L, and the concentration of the 1,3,5-benzenetricarboxylic acid chloride in the organic phase solution is 1 g / L.
2. The method for preparing the cellulose acetate-based interfacial polymerization flat nanofiltration membrane according to claim 1, characterized in that: The mass fraction of cellulose acetate in the cellulose acetate casting solution in step (1) is 16-20%.
3. The method for preparing the cellulose acetate-based interfacial polymerization flat nanofiltration membrane according to claim 1, characterized in that: The specifications of the cellulose acetate raw material in step (1) are: 39.8 wt% acetyl content and a molecular weight of 30,000.
4. The method for preparing the cellulose acetate-based interfacial polymerization flat nanofiltration membrane according to claim 1, characterized in that: The aqueous phase monomer in the aqueous phase solution of step (3) is one of diethylenetriamine, polyethyleneimine, piperazine, m-phenylenediamine, 1,3-cyclohexanebis(methylamine), and triethylenetetramine.
5. The method for preparing the cellulose acetate-based interfacial polymerization flat nanofiltration membrane according to claim 1, characterized in that: The aqueous phase monomer in the aqueous phase solution of step (3) is diethylenetriamine.
6. The method for preparing the cellulose acetate-based interfacial polymerization flat nanofiltration membrane according to claim 1, characterized in that: The drying in step (3) is carried out in an oven at 60°C for 5-10 min.
7. A cellulose acetate-based interfacial polymerization flat nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-performance composite forward osmosis membrane and preparation method thereof
CN108452685A
Preparation method of regenerated cellulose ultrafiltration membrane with controllable product performance and product
CN114653214A